GLI1 Immunohistochemistry Distinguishes Mesenchymal Neoplasms With GLI1 Alterations From Morphologic Mimics. (23rd April 2023) - Parrack, Paige H.; Mariño-Enríquez, Adrian; Fletcher, Christopher D.M.; Hornick, Jason L.; Papke, David J.
Abstract : Glioma-associated oncogene 1 ( GLI1 ) alterations have been described in pericytoma with t(7;12), gastroblastoma, plexiform fibromyxoma, and an emerging class of GLI1 -rearranged or amplified mesenchymal neoplasms including "nested glomoid neoplasm". The immunophenotype of these tumor types is nonspecific, making some cases difficult to diagnose without sequencing. The utility of GLI1 immunohistochemistry (IHC) in distinguishing nested glomoid neoplasms and pericytomas with t(7;12) from morphologic mimics is unknown. To investigate the diagnostic value of GLI1 IHC, we determined its sensitivity and specificity in a "test cohort" of 23 mesenchymal neoplasms characterized by GLI1 alterations, including 12 nested glomoid neoplasms (7 GLI1 -rearranged, 4 GLI1 amplified, and 1 unknown GLI1 status), 9 pericytomas with t(7;12), 1 gastroblastoma, and 1 malignant epithelioid neoplasm with PTCH1 :: GLI1 fusion. GLI1 IHC was 91.3% sensitive in this cohort; all tumors except 2 pericytomas with t(7;12) expressed GLI1. GLI1 was also expressed in 1 of 8 (12%) plexiform fibromyxomas. Nineteen of 22 GLI1-positive tumors showed nuclear and cytoplasmic staining, while 3 showed nuclear staining only. GLI1 IHC was 98.0% specific; among morphologic mimics [40 well-differentiated neuroendocrine tumors, 10 atypical lung carcinoids, 20 paragangliomas, 20 glomus tumors, 20 solitary fibrous tumors, 10 Ewing sarcomas, 10 alveolar rhabdomyosarcomas (ARMS), 10 BCOR -altered sarcomas, 10 myoepitheliomas, 9 myopericytomas, 9 epithelioid schwannomas, 9 ossifying fibromyxoid tumors, 10 biphasic synovial sarcomas, 10 PEComas, 31 gastrointestinal stromal tumors, 10 inflammatory fibroid polyps, 11 pseudoendocrine sarcomas], 5 of 249 tumors expressed GLI1 (2 well-differentiated neuroendocrine tumors, 1 ARMS, 1 Ewing sarcoma, 1 BCOR -altered sarcoma). GLI1 IHC was also performed on a separate cohort of 13 molecularly characterized mesenchymal neoplasms in which GLI1 copy number gain was identified as a putatively secondary event by DNA sequencing (5 dedifferentiated liposarcoma [DDLPS], 2 adenosarcomas, 2 unclassified uterine sarcomas, 1 leiomyosarcoma, 1 ARMS, 1 intimal sarcoma, 1 osteosarcoma); 2 DDLPS, 1 ARMS, and 1 unclassified uterine sarcoma expressed GLI1. Lastly, because pleomorphic sarcomas sometimes show GLI1 amplification or copy number gain, GLI1 IHC was performed on a separate "pleomorphic sarcoma" cohort: GLI1 was expressed in 1 of 27 DDLPS, 1 of 9 leiomyosarcomas, and 2 of 10 pleomorphic liposarcomas, and it was negative in 23 well-differentiated liposarcomas and 9 unclassified pleomorphic sarcomas. Overall, GLI1 IHC was 91.3% sensitive and 98.0% specific for mesenchymal tumor types with driver GLI1 alterations among morphologic mimics. GLI1 expression was less frequent in other tumor types with GLI1 copy number gain. Given its specificity, in the appropriate morphologic context, GLI1 IHC may be a useful diagnostic adjunct for mesenchymal neoplasms with GLI1 alterations.